PRELIMINARY INVENTORY OF THE SMALL MAMMAL FAUNA OF THE YOK DON NATIONAL PARK (DAK LAK PROVINCE, VIETNAM) - S. V., Kruskop; A. V., Abramov; A. V., Shchinov; Nguyen, Huu Thuc (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
Three short surveys of mammals were held in 2007 (June, beginning of rain season) and 2012 (May, low season, and December, beginning of dry season) in Yok Don National Park (Vietnam, Dak Lak Province) under the aegis of Joint Vietnam-Russia Tropical Science and Technology Research Centre. Occurrence of 23 small mammal species was revealed including 13 species new to Dak Lak Province. The latter are represented mainly by bats of which the most important records are Murina harrisoni, Pipistrellus paterculus and Hesperoptenus tickelli, and also by rats (Rattus cf. andamanensis, Berylmys bowersi) and white-toothed shrew Crocidura phanluongi. Tree-shrew (Tupaia belangeri) was the most abundant non-volant mammal during the survey. On the whole, the micromammalian fauna of Yok Don seems to be strongly underestimated.